Language Dilemmas in the EFL Class: Historical and Political Factors - Asmawati Asmawati; Fithrah Nurul Hidayah; Hafez Al Assad; Sholihatul Hamidah Daulay; Maslathif Dwi Purnomo (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2024)
This research explains the complex and many-sided landscape of English language teaching (ELT) and how historical and political contexts influence it. By acknowledging the deep roots of ELT, this research highlights the importance of understanding the challenges and opportunities faced in teaching and learning English in various contexts. The authors conducted extensive library research to gather data and insights into the complexities of language learning in the EFL context, providing valuable solutions for addressing these challenges. Moreover, the article offers a historical review of the Dutch occupation of Indonesia and how it impacted education and English language teaching in the region. By exploring the historical context, the article highlights the significance of acknowledging the past and its influence on present-day ELT practices.